Association of cervical spine signs and symptoms with temporomandibular disorders in adults: a systematic review protocol. Issue 6 (8th June 2020) - Balthazard, Pierre; Hasler, Véronique; Goldman, Daniel; Grondin, Francis
ABSTRACT: Objective: The objective of this systematic review is to assess the evidence of association of cervical spine signs and symptoms with temporomandibular disorders (TMD). This will help to lend credence to mechanisms supporting the association in order to improve care strategies for this condition. Introduction: The association of cervical spine impairments (in relation to neck posture, cervical spine mobility, muscle tenderness, muscle activity, and neck disability) with TMD has been widely discussed in the literature. Clarification of this relationship is important for health professionals to better assess and treat TMD. Inclusion criteria: Eligible studies will include participants aged 18 years and over, with a diagnosis of TMD from the Research and Diagnostic Criteria for Temporomandibular Disorders or a revised version. Exclusion criteria will be participants with previous temporomandibular joint surgery, history of trauma or fracture in the temporomandibular joint or the craniomandibular system; serious comorbid conditions such as cancer, rheumatic disease, and neurological problems; primary cervical spine disorders such as disc herniation or spinal degenerative changes; or systemic disease such as ankylosing spondylitis. Methods: The search for articles will be conducted in the databases PubMed, PEDro, CINAHL, Web of Science, and Embase, without language or time restrictions. Two independent reviewers will review the title, abstract, and full texts of identified studies; select studies against the inclusion criteria; assess the methodological quality of eligible studies using critical appraisal tools; and perform data extraction. Relevant quantitative data will be pooled with statistical meta-analysis, when possible. Systematic review registration number: PROSPERO CRD42019123698.